Core–shell cellulose nanofibers for biocomposites – Nanostructural effects in hydrated state. (10th July 2015) - Prakobna, Kasinee; Terenzi, Camilla; Zhou, Qi; Furó, István; Berglund, Lars A.
Highlights: Core–shell cellulose/xyloglucan nanocomposites. Excellent hygromechanical properties. Mechanical properties of wet gels, soaked films, and solid films. Nanostructure effects on molecular mobility of water. Abstract: Core–shell wood cellulose nanofibers (CNF) coated by an XG hemicellulose polymer are prepared and used to make biocomposites. CNF/XG biocomposites have interest as packaging materials and as hydrated CNF/XG plant cell wall analogues. Structure and properties are compared between Core–shell CNF/XG and more inhomogeneous CNF/XG. Experiments include XG sorption, dynamic light scattering of CNF nanoparticle suspensions, FE-SEM of nanostructure, moisture sorption, tensile testing in moist conditions and dynamic mechanical analysis. 2 H NMR relaxometry is performed on materials containing sorbed 2 H2 O2 in order to assess water molecular dynamics in different materials. The results clarify the roles of CNF, XG and the CNF/XG interface in the biocomposites, both in terms of moisture sorption mechanisms and mechanical properties in moist state. The concept of core–shell nanofiber network biocomposites, prepared by filtering of colloids, provides improved control of polymer matrix distribution and interface structure. Also, present mechanical properties are much superior to comparable plant fiber biocomposites.